Chromosome Level Genome Assembly of Andrographis paniculata - Liang, Ying; Chen, Shanshan; Wei, Kunhua; Yang, Zijiang; Duan, Shengchang; Du, Yuan; Qu, Peng; Miao, Jianhua; Chen, Wei; Dong, Yang (Frontiers in Genetics, 2020)
Andrographis paniculata (Chinese name: Chuanxinlian) is an annual dicotyledonous medicinal plant widely grown in China and Southeast Asia. The dried plant has a highly acclaimed usage in the traditional Chinese medicine for its antipyretic, anti-inflammatory, and analgesic effects. In order to help delineate the biosynthetic pathways of various secondary metabolites, we report in this study a high-quality reference genome for A. paniculata. With the help of both PacBio single molecule real time sequencing and Illumina sequencing reads for error correction, the A. paniculata genome was assembled into a total size of 284 Mb with a contig N50 size of 5.14 Mb. The contigs were further assembled into 24 pseudo-chromosomes by the Hi-C technique. We also analyzed the gene families (e.g. CPS, KSL, and CYP450) whose protein products are essential for synthesizing bioactive compounds in A. paniculata. In conclusion, the high-quality A. paniculata genome assembly builds the foundation for decoding the biosynthetic pathways of various medicinal compounds.